Membangun Kesadaran Investasi Syariah pada Generasi “Z” dengan Penerapan Model Edukasi Pasar Modal - Dito Rinaldo; vina Anggilia Puspita (Jurnal Dharma Bhakti Ekuitas, 2025)
The low literacy level of the sharia capital market in Indonesian society emphasises the significance of early education initiatives. Previous research found that more than half of the Java students surveyed were not actively engaging in the stock market. Based on the actual occurrence, the goal of this community service program (PKM) is to educate SMK Baabul Kamil Jatinangor students about the Sharia capital market. The PKM programme will use 5 capital market education model materials for stages 1 and 2, namely: lifestyle education, financial planning education, education on the halal idea of sharia capital markets, basic capital market concepts, and a comparison between sharia and conventional capital markets. This PKM program was successful in boosting students' capital market literacy from an average score of 1.125 (very low) to 2.945 (low ). Because the PKM program only applies stage "1" and a portion of stage "2" in the capital market education model, the next PKM program can continue stages "2' and "3" as a whole in the capital market education model and add practical content to each educational material to significantly increase literacy. The PKM program must also engage other stakeholders, such as the Indonesia Stock Exchange (BEI) and the capital market investor community. This attempts to provide participants with views from multiple parties with varying expertise, experience, and viewpoints, allowing for additional references to be utilised in dealing with various circumstances that may arise during capital market investing activities. Keywords: Education, Investment, Islamic Capital Market and Islamic Stocks. Abstrak Rendahnya literasi pasar modal syariah masyarakat Indonesia mendorong pentingnya program edukasi sejak dini.  Hasil penelitian sebelumnya menujukan lebih dari 50% mahasiswa di pulau jawa yang dijadikan sample belum terlibat secara aktif di pasar modal. Berdasarkan fenomena yang ada, maka program PKM ini bertujuan memberikan edukasi pasar modal syariah kepada siswa SMK Baabul Kamil Jatinangor. Program PKM akan menggunakan 5 materi model edukasi pasar modal tahap 1 dan 2,  yaitu lifestyle education, financial planning education, education on the halal concept of syariah capital market, Basic concept of capital market and the comparison between syariah and conventional capital market.  Program PKM ini berhasil meningkatkan literasi pasar modal siswa yang sebelumnya memiliki rata-rata skor 1,125 (sangat buruk) menjadi 2,945 (rendah/mendekati cukup). Dikarenakan program PKM hanya menerapkan tahapan “1” dan Sebagian tahap “2” pada model edukasi pasar modal, untuk itu program PKM selanjutnya dapat meneruskan tahapan  “2’ dan “3”  secara menyeluruh pada model edukasi pasar modal, serta menambah muatan praktek pada setiap materi edukasi agar literasi meningkat secara signifikan, selain itu juga  program PKM perlu melibatkan pihak terkait lainnya seperti Bursa Efek Indonesia (BEI) dan komunitas investor pasar modal. Hal ini bertujuan agar peserta menerima indiside dari berbagai pihak yang memiliki pengetahuan, pengalaman dan perspektif yang berbeda, sehingga lebih banyak referensi yang dapat digunakan dalam menghadapi berbegai situasi yang mungkin terjadi pada saat praktek investasi pasar modal. Kata kunci: Edukasi, Investasi, Pasar Modal Syariah dan Saham Syariah.